Measurements of the Sound Absorption Coefficient of Auditorium Seats for Various Geometries of the Samples - RUBACHA, Jarosław; PILCH, Adam; ZASTAWNIK, Marcin (Archives of Acoustics, 2012)
This paper presents the results of measurements of the sound absorption coefficient of auditoriumseats carried out in the laboratory using two methods. In the first one, small blocks of seats in variousarrangements were studied in a reverberation chamber to determine the absorption coefficient of anauditorium of infinite dimensions. The results were compared to the values of the absorption coefficientmeasured using the second method, which involved samples enclosed within a frame screening the sidesurfaces of other auditorium blocks. The results of both methods allowed for the assessment of the soundabsorption coefficient of an auditorium of any dimensions while taking into account the sound absorptionby the side surfaces. The method developed by the authors will simplify the currently known measurementprocedures.